IMPLEMENTATION OF LAW NUMBER 33 OF 2014 CONCERNING HALAL PRODUCT ASSURANCE IN PEKIRINGAN VILLAGE - Yanti Romlahayati; Alisha Fasya Khoirunissa; Aulia Rahmawati; Cahya Hilda Laela; Shifaniya Isnaeni (Jurnal Abdisci, 2024)
This study analyzes the implementation of Law Number 33 of 2014 concerning Halal Product Assurance in Pekiringan Village, Kesambi District, Cirebon City. This law requires products circulating in Indonesia to have a halal certificate to increase consumer confidence and competitiveness of local products, especially MSMEs. The research method used is empirical juridical, with data collected through interviews and observations. The results of the study show that many MSMEs in Pekiringan Village do not have halal certificates. The main obstacles are the lack of information about the certification procedure, the low awareness of the importance of halal certificates, and the limitations in understanding the technology required for registration. More intensive socialization, education, and technical assistance are needed to increase the participation of MSMEs in the halal certification program.